Simulating Torque Converter on a 3 GTs Fishing Vessel using Computational Fluid Dynamics. (November 2019) - Zulkifly,; Baharuddin,; Rivai, H; Firmansyah, M R; Santoso, T M
Abstract: Torque converter is needed to reduce the difference distance on an engine power curve and propeller operating load curve. Torque converter works by removing and cutting the flow of power from engine to transmission shaft automatically in order to adjust with fluctuative propeller load. Torque converter works on a fluid clutch principal hence it has ability to absorb and reduce excessive torque moments. This research aims to determine the effect of impeller distance against dynamic characteristics of torque converter on a 3 GT fishing vessel. Based on the designed torque converter dimension, a simulation using computational fluid dynamics (CFD) in an ANSYS 16.0 simulation software was conducted. The simulation was done on three distances between impellers i.e. 2.5 mm, 5 mm, and 7.5 mm and on five rotations i.e. 600 rpm, 1000 rpm, 1400 rpm, 1800 rpm, and 2200 rpm. Information obtained from the CFD simulation includes: pressure and shear stress distribution on impeller, flow velocity on the torque converter shell, torque value, as well as maximum transmission power of torque converter. The result shows that the ideal impeller gap for the 3 GTs fishing vessel from the dynamic characteristics parameter of torque converter is 7.5 mm.